2004
DOI: 10.1111/j.0143-2885.2004.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic treatment of dens invaginatus type III with three root canals and open apical foramen

Abstract: The present case demonstrated that conservative root canal treatment can be performed successfully even in sever cases of dens invaginatus. The use of a dental operating microscope can help in the management of complicated cases of invaginated teeth through conventional root canal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 32 publications
(78 reference statements)
0
87
0
Order By: Relevance
“…MTA is both of biocompatibility and it is less cytotoxic because of its alkaline pH 22 . Due to the presence of calcium and phosphate ions in MTA, it can support cementum deposition 23 .…”
Section: Discussionmentioning
confidence: 99%
“…MTA is both of biocompatibility and it is less cytotoxic because of its alkaline pH 22 . Due to the presence of calcium and phosphate ions in MTA, it can support cementum deposition 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional radiography plays an important role in evaluating the complex morphology of the root canal system, but it only provides two-dimensional representation of a three-dimensional structure 2) . Non-surgical endodontic management can be achieved even in complicated cases of dens invaginatus by diagnosis and treatment planning using …”
Section: Discussionmentioning
confidence: 99%
“…CBCT scans 1,3,9,[11][12][13] and microscopic treatment technique 2,3,12) . In the present case, the CBCT images revealed that the root canals and area of invagination had a highly complex morphology, indicating that appropriate management would require the use of a dental operating microscope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations